Synthesis of fibres by growth-packing - Yoon, Han Sik (Nature Publishing Group, 1987)
Molecular growth and self-ordering, the process that gives rise to wool, cotton and other fibrous biological materials, has until now been observed only in nature. Controversy exists as to whether these fibrillar elements have fundamental significance in relation to bio-synthesis or whether they are simply secondary aggregation phenomena after molecular bonding has been completed1. Since the initial attempt by Staudinger in 19272, numerous attempts at simulation of such growth-packing of artificial fibres have been made without success; Pennings et al.3 effected chain packings with polyethylene in a xylene solution, but without molecular growth. Here I report the first synthesis of fibres from poly-p-phenylene-terephthalamide (PPT-A) by means of a growth-packing mechanism4 (Fig. 1). They were grown in a stationary gel phase, containing active oligo-PPT-A, heterocyclic tertiary amines, alkali metal cations and a polar solvent. Molecular growth seemed to be attained in an orderly gel phase, in which the critical chain distance between polymer molecules was maintained at 2.4 nm on average by solvent bridges, built by induced polarizing forces between the polar groups in the chains. After the growth of the molecules, the chain packing took place, with lateral movement of the grown molecules due to the collapse of the solvent bridges. The fibres thus formed have some similarity to native flax or ramie fibres.